2005
DOI: 10.1038/sj.leu.2403868
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic interactions between MEK1/2 and histone deacetylase inhibitors in BCR/ABL+ human leukemia cells

Abstract: Interactions between the histone deacetylase inhibitor SAHA and the pharmacologic MEK1/2 inhibitor PD184352 were examined in Bcr/Abl þ human leukemia cells. Coadministration of minimally toxic concentrations of SAHA (or sodium butyrate) and PD184352 (or U0126) resulted in a synergistic increase in mitochondrial damage, caspase activation, and apoptosis in K562 and LAMA 84 cells. Similar interactions were observed in CD34 þ cells from two patients with CML and in imatinib mesylate-resistant K562 cells but not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
49
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 41 publications
6
49
0
Order By: Relevance
“…The majority of the antiproliferative effect observed in treatment of the K562 CML cell line was secondary to MEK inhibition, consistent with other studies using MEK inhibitors in this cell line (6,(19)(20)(21)(22). Although MEK inhibition appears to have a biphasic dose-response effect on erythroid differentiation in K562 cells (23), it demonstrated a dose-dependent inhibitory effect on erythroid precursors in our patient-derived cells, suggesting a difference in underlying MAPK and erythropoietin receptor (EPO-R) signaling in these differing contexts.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The majority of the antiproliferative effect observed in treatment of the K562 CML cell line was secondary to MEK inhibition, consistent with other studies using MEK inhibitors in this cell line (6,(19)(20)(21)(22). Although MEK inhibition appears to have a biphasic dose-response effect on erythroid differentiation in K562 cells (23), it demonstrated a dose-dependent inhibitory effect on erythroid precursors in our patient-derived cells, suggesting a difference in underlying MAPK and erythropoietin receptor (EPO-R) signaling in these differing contexts.…”
Section: Discussionsupporting
confidence: 77%
“…Several other studies have demonstrated that pharmacologic inhibition of MAPK signaling can increase cell death and decrease cell proliferation in CML cells in vitro (6,(19)(20)(21)(22)24). In a competing fates model of BCR-ABL1 inhibition by inhibitors, such as imatinib and dasatinib, cells typically commit to apoptosis more rapidly than they can restore responses to growth factor-induced survival signals (25).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (29) suggested that the downregulation of the endogenous ROS scavenger thioredoxin is associated with SAHA-induced ROS-dependent apoptosis. Moreover, ROS generation plays a crucial role in synergistic apoptosis caused by the combinations of HDIs and various compounds such as the proteasome inhibitor bortezomib, the purine analogue fludarabine, the MAP/ERK kinase 1/2 inhibitor PD184352, the alkyllysophospholipid perifosine, and the multiple receptor tyrosine kinase inhibitor AEE788 (30)(31)(32)(33)(34). The present study suggests that ROS generation through HDAC inhibition leads to caspase-dependent apoptosis caused by HDIs/15d-PGJ 2 .…”
Section: Discussionmentioning
confidence: 82%
“…23 Specific blockade of this pathway by bortezomib synergistically potentiates HDACI-induced apoptosis of myeloid leukemia cells. 24,25 In addition to inactivation of NF-kB, bortezomib and SAHA together could inhibit the upstream regulators of ERK pathway, such as Raf-1, MEKK-1 and MEKK-2 in T-leukemia/lymphoma cells, resulting in downregulation of MEK and ERK phosphorylation. These findings further underline the functional complementation of both agents in the inhibition of the ERK pathway.…”
Section: Discussionmentioning
confidence: 99%